Circulating levels of FSH-h alpha subunit, FSH and LH in peripheral blood during the menstrual cycle and after stimulation with synthetic gonadotropin hormone (LH-RH) (Colombia Medica, 1986)
The concentration of the alpha subunit of human FSH (h-FSH) was measured in serum throughout normal menstrual cycles and when LH-RH was administered on the first and second days of menstruation. In moral cycles, the alpha h-FSH subunit was shown to circulate in the free form, with the highest concentration occurring at the midcycle peak of LH and FSH. The concentration of the alpha h-FSH subunit during the follicular phase was not significantly different from that observed during the cycle's luteal phase.The response to the administration of different concentrations of LH-RH (10ug and 100ug) is an increase in circulating levels of alpha h-FSH subunit directly related to the increases in LH and FSH.